2020
DOI: 10.1371/journal.pone.0222375
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci for traits linked to fusarium head blight in barley

Abstract: Fusarium head blight (FHB) is a devastating disease occurring in small grain cereals worldwide. The disease results in the reduction of grain yield, and mycotoxins accumulated in grain are also harmful to both humans and animals. It has been reported that response to pathogen infection may be associated with the morphological and developmental traits of the host plant, e.g. earliness and plant height. Despite many studies, effective markers for selection of barley genotypes with increased resistance to FHB hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 104 publications
(154 reference statements)
2
10
1
Order By: Relevance
“…Similarly, high genetic variation for heading ( Zanke et al, 2014 ), anthesis ( Bogard et al, 2011 ), spike length ( Zhai et al, 2016 ), and FLA ( Liu et al, 2017 , 2018 ) has been reported in winter wheat. These traits are important for agronomic adaptation and can have pleiotropic effects on disease severity, which may delay the use of resistance alleles in commercial cultivars ( Gervais et al, 2002 ; Buerstmayr et al, 2020 ; Ogrodowicz et al, 2020 ). However, in this present study, we found very weak correlations between AUDPC (FHB) and all five agronomic traits measured.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, high genetic variation for heading ( Zanke et al, 2014 ), anthesis ( Bogard et al, 2011 ), spike length ( Zhai et al, 2016 ), and FLA ( Liu et al, 2017 , 2018 ) has been reported in winter wheat. These traits are important for agronomic adaptation and can have pleiotropic effects on disease severity, which may delay the use of resistance alleles in commercial cultivars ( Gervais et al, 2002 ; Buerstmayr et al, 2020 ; Ogrodowicz et al, 2020 ). However, in this present study, we found very weak correlations between AUDPC (FHB) and all five agronomic traits measured.…”
Section: Discussionmentioning
confidence: 99%
“…isolates, inoculation method, plant development and morphology. Hence, exploitation of FHB QTL is challenging because resistance appears to be exclusively quantitative in elite barley cultivars and determines the basal level of infection [20,[44][45][46]. Additionally, basal FHB resistance is associated with different components (resistance types I to VI) contributing independently to different layers of defence, which are often not equally cumulated or strongly expressed in one genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Plants were cultivated in the phytotron of the Plant Cultivation Center of the Institute of Plant Genetics, Polish Academy of Sciences, Poland, Poznań. Barley genotypes came from recombinant inbred lines of Hordeum vulgare MCam, obtained from the cross between the Polish cultivar Lubuski and a Syrian breeding line—Cam/B1/CI08887//CI05761—selected from the materials of the Institute of Plant Genetics, Polish Academy of Sciences on the basis of previous studies [ 14 ]. Two extremely different lines of barley—the MCam 88 line (hereafter referred to as Hs) and the resistant MCam 59 line (hereafter referred to as Hr)—were taken for metabolomic analysis.…”
Section: Methodsmentioning
confidence: 99%